The impact of warming on the growth of the cabbage moth population in the Western Forest-Steppe conditions - Snizhok, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To study the peculiarities of the biology and population control of the cabbage moth on winter rapeseed crops. Methods. Field — methods commonly used in entomology and plant protection to study the species composition of pests and entomophages, the dynamics of their numbers and harmfulness, and to evaluate the effectiveness of chemical methods of crop protection; laboratory — clarification of the species composition of phytophages and entomophages; mathematical and statistical — establishing the reliability of the results obtained; computational — determining the economic effectiveness of chemical protection of winter rapeseed from a complex of pests. Results. Based on observations, the phenology of the cabbage moth on winter rapeseed crops in the Western Forest-Steppe region has been compiled. It has been noted that the flight of butterflies in spring begins in the Forest-Steppe and Polissya regions at the end of April. At an average daily air temperature of 14—18°C and a GTK of 2.3 the caterpillars appear in 9—12 days, and at 20—25°C and a GTK of 1.5, in 4—7 days. Studies have shown that the harmfulness of cabbage moth caterpillars depends on weather conditions. This is because feeding intensity increases at higher temperatures and low air humidity. At a GTK of 0.37, damage to winter rapeseed plants was 60%, and when the GTK increased to 2.96, damage to plants by cabbage moth caterpillars was three times less. As studies have shown that the most effective control methods are sowing dates and the use of insecticides. The optimal sowing dates for the area were August 15 to 20. Damage to early crops by cabbage moth caterpillars was 15.0%. During the period of the first true leaf appearance, this indicator did not exceed 16.7% with a damage score of 1.28. In late sowing crops, plant damage was more than twice as high, reaching 47.0%. It was noted that the effectiveness and period of protective action of insecticides are different. The highest technical effectiveness (80.2%) against cabbage moth caterpillars was observed on the 10 day after emergence in variants with the active ingredient thiamethoxam. When spraying with insecticides during the emergence phase of winter rapeseed, the highest effectiveness was observed in preparations based on active ingredients such as lambda cyhalothrin and dithemoate. Conclusions. In the conditions of the Western Forest-Steppe, the main factors in regulating damage to plants by the cabbage moth in the autumn period on winter rapeseed crops are sowing dates and chemical protection. The optimal sowing dates for the zone are August 15—20. The most effective insecticide for pre-sowing seed treatment was one with the active ingredient thiamethoxam, which had a technical efficiency of 80.2%. When spraying winter rapeseed seedlings, preparations with the active ingredient lambda cyhalothrin and dithimoate provided an effectiveness of 85.1—94.7%.